2023
DOI: 10.1007/s00417-023-06057-6
|View full text |Cite
|
Sign up to set email alerts
|

Contrast sensitivity function under three light conditions in patients with type 1 diabetes mellitus without retinopathy: a cross-sectional, case–control study

Abstract: Purpose To determine whether patients with type 1 diabetes mellitus (T1DM), without any sign of diabetic retinopathy, have any alteration in Contrast Sensitivity Function (CSF), in relation to patients without this disease, and whether CSF assessment in three different light conditions can be an effective test in the early detection of diabetic retinopathy. Methods A prospective, cross-sectional, case-control study was preformed including 80 patients (40 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…The study concluded that individuals with DR exhibited a substantial reduction in CS across a wide range of spatial frequencies. The findings have been supported by recent research publications, which echo similar conclusions [111][112][113]. While some diabetic patients without clinically evident DR may also demonstrate decreased CS, this effect was less consistent, and the affected frequencies varied.…”
Section: Contrast Sensitivitysupporting
confidence: 83%
See 1 more Smart Citation
“…The study concluded that individuals with DR exhibited a substantial reduction in CS across a wide range of spatial frequencies. The findings have been supported by recent research publications, which echo similar conclusions [111][112][113]. While some diabetic patients without clinically evident DR may also demonstrate decreased CS, this effect was less consistent, and the affected frequencies varied.…”
Section: Contrast Sensitivitysupporting
confidence: 83%
“…These changes in visual function suggest that retinal neuronal damage may precede overt vascular lesions in DR, potentially enabling early detection through CS testing. However, longitudinal studies are warranted to establish CS as a reliable biomarker for predicting DR onset and progression, strengthening evidence for its application in early screening and monitoring [112].…”
Section: Contrast Sensitivitymentioning
confidence: 99%